Evaluation of Chitosan/Fructose Model as an Antioxidant and Antimicrobial Agent for Shelf Life Extension of Beef Meat During Freezing - Shaheen Mohmed S.; Shaaban Hamdy A.; Hussein Ahmed M.S.; Ahmed Mohamed B.M.; El-Massry Khaled; El-Ghorab Ahmed (Polish Journal of Food and Nutrition Sciences)
In the present study the effect of chitosan/fructose Maillard reaction products (CF-MRPs) as antioxidant and antimicrobial agents was evaluated and applied on minced beef meat during frozen storage. Antioxidant and antimicrobial properties of chitosan-fructose complexes were tested. Anti-oxidant properties were measured by the DPPH, β-carotene and ABTS methods. These three methods showed the same profile of antioxidant activity. Chitosan with 4% fructose autoclaved for 45 min (CF9) showed to have the most effective antioxidant activity. It was demonstrated that the browning product exhibited antioxidant activity. For antimicrobial activity, most chitosan-fructose complexes were less effective than chitosan. Thus, MRPs derived from chitosan-sugar model system can be promoted as a novel antioxidant to prevent lipid oxidation in minced beef. Chitosan-sugar complex could be a potential alternative natural product for synthetic food additive replacement that would additionally meet consumer safety requirement.